2022
DOI: 10.1002/brb3.2604
|View full text |Cite
|
Sign up to set email alerts
|

Therapy outcome of day treatment for people with anorexia nervosa before and during the COVID‐19 pandemic

Abstract: Objective: The current research aimed to compare clinical outcome measures of two National Eating Disorder (ED) Day Services at the Maudsley Hospital from before the COVID‐19 lockdown, when treatment was face to face, with after the lockdown when treatment moved online. Method: Clinical outcome measures collected as part of the admission and discharge process were compared from the beginning and end of treatment for patients treated either via face‐to‐face or online delivery. Twenty‐nine patients’ data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…The clinical effectiveness of online treatment during the pandemic, compared to in-person care prepandemic, was examined in uncontrolled ( n = 55–159) [ 38 , 40 ] and small, nonrandomized controlled studies ( n = 9–365) [ 65 , 73 76 ]. Although the results are preliminary, the switch to online treatment as an alternative for in-person treatment was found to be as effective, safe, and well-tolerated as face-to-face treatment in most studies in outpatients [ 65 , 73 75 , 77 ▪ ].…”
Section: Online Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical effectiveness of online treatment during the pandemic, compared to in-person care prepandemic, was examined in uncontrolled ( n = 55–159) [ 38 , 40 ] and small, nonrandomized controlled studies ( n = 9–365) [ 65 , 73 76 ]. Although the results are preliminary, the switch to online treatment as an alternative for in-person treatment was found to be as effective, safe, and well-tolerated as face-to-face treatment in most studies in outpatients [ 65 , 73 75 , 77 ▪ ].…”
Section: Online Treatmentmentioning
confidence: 99%
“…In most studies, clinical effectiveness on weight gain and psychopathology was found to be similar before and after the switch to online treatment [73][74][75]. One controlled study observed that face-to-face day treatment for patients with AN resulted in higher rates of weight restoration in comparison to online day treatment [76].…”
Section: Online Treatmentmentioning
confidence: 99%
“…Despite being designed as an in‐person intervention, elements of SPEAKS worked well being delivered online, but for the experiential sessions, it was widely felt by patients and therapists that in‐person sessions were preferable. Research specific to AN treatment delivery and outcomes, such as findings from Carr et al (2022), found no significant advantage for either in‐person or online delivery. Furthermore, experiential methods such as chairwork are reported to be feasibly delivered online (Pugh et al, 2021), suggesting that factors such as patient preference and therapist confidence in delivery have influence over how these are received This study adds to those previous findings by highlighting views of online therapy for this specific patient group.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, the systematic review by Sideli and colleagues [ 16 ] found the worsening of symptoms to occur more often in individuals with self-reported ED than in those attending ED services. Carr and colleagues [ 17 ] compared online treatment after the beginning of the pandemic to the previously delivered face-to-face day service treatment and found it effective in decreasing EDE-Q scores but not for weight improvement. These data point to the need for a better characterization of individuals with ED who attended specialized services during the pandemic, in order to evidence both differential (e.g., with respect to either the pre-existence or the severity of the disorder) areas of vulnerability and protective factors connected to specific aspects of the treatment delivered.…”
Section: Introductionmentioning
confidence: 99%